2013
DOI: 10.1016/j.jpedsurg.2012.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Development of an artificial placenta V: 70h veno-venous extracorporeal life support after ventilatory failure in premature lambs

Abstract: Purpose An artificial placenta would change the paradigm of treating extremely premature infants. We hypothesized that using a veno-venous extracorporeal life support (VV-ECLS) artificial placenta after ventilatory failure would stabilize premature lambs and maintain normal fetal physiologic parameters for 70h. Methods A near-term neonatal lamb model (130 days; term=145) was used. The right jugular vein (drainage) and umbilical vein (reinfusion) were cannulated with 10–12 Fr cannulas. Lambs were then transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 31 publications
0
40
0
Order By: Relevance
“…Despite cannulation of the aorta via the umbilical artery, we could not solve the problem of persistent hypotension. We transitioned to a model of venovenous (VV) ECLS with jugular drainage and umbilical reinfusion and supported lambs for up to 92 hours [13, 16]. We found that this model of an AP provided adequate perfusion to the brain despite the ligation of one carotid artery for monitoring line placement [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite cannulation of the aorta via the umbilical artery, we could not solve the problem of persistent hypotension. We transitioned to a model of venovenous (VV) ECLS with jugular drainage and umbilical reinfusion and supported lambs for up to 92 hours [13, 16]. We found that this model of an AP provided adequate perfusion to the brain despite the ligation of one carotid artery for monitoring line placement [17].…”
Section: Discussionmentioning
confidence: 99%
“…Research in our laboratory initially involved a pumpless arteriovenous system and a pump-driven venoarterial system [12]. Our current model involves pump-driven venovenous ECLS; we previously reported its use to support near-term fetal lambs for 70 hours after initial failure of conventional mechanical ventilation [13]. The purpose of this study was to examine the AP's efficacy a) in providing prolonged support up to one week, b) in supporting extremely premature lambs that more closely model the human ELGAN, and c) as compared to the current standard of care in neonatal intensive care units.…”
Section: Introductionmentioning
confidence: 99%
“…In premature lambs, mechanical ventilation failed within one hour and subsequently 6 of 7 lambs were then successfully transitioned to the AP and survived for 24 hours. [47**] Subsequent work has focused on sheep models of extreme prematurity (equivalent to a 24 week human), lung development, brain function, development of nonthrombogenic surfaces, and survival after weaning from the AP. While much progress has been made, many challenges remain to model development and clinical translation (Table 2).…”
Section: The Artificial Placenta: Recent Advancesmentioning
confidence: 99%
“…The first attempts to develop an artificial placenta as an effective alternation to provide respiratory support for newborns, especially preterm were made in mid-20th century [2]. Since, then for many decades it has fascinated the imaginations of researchers as an alternative approach to help extremely preterm infants (EPIs) born less than 28 weeks of gestation to overcome respiratory insufficiency [3,4].…”
mentioning
confidence: 99%
“…Even conventional extracorporeal life support or extracorporeal membrane oxygenation (ECLS/ECMO) causes severe damage to immature lungs, and is contraindicated in extremely low gestational age newborns (ELGANs) [24]. Hence, the best way to save such neonates is through use of artificial placenta that helps in maintaining fetal circulation and bypassing lungs, thus obviating the need for mechanical ventilation and allowing the lungs to mature [4]. …”
mentioning
confidence: 99%